2011
DOI: 10.1080/13632469.2011.560361
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Rectangular Spiral Shear Reinforcement on Infilled R/C Frames Under Cyclic Loading

Abstract: The effect of two types of shear reinforcement, with reference to two types of masonry infills, on the seismic performance of reinforced concrete (RC) frames was experimentally investigated. Six single-story, one-bay, 1/3-scale frame specimens were tested under cyclic horizontal loading, up to a drift level of 40‰. Bare frames and infilled frames with two different infill compressive strengths were sorted into two groups based on stirrups or spirals as shear reinforcement. From the observed responses it can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…(1), (6), and (9), respectively. The calculated and the experimentally measured cracking angles of the tested specimens are presented in Table 2.…”
Section: Inclination Of Torsional Crackingmentioning
confidence: 98%
See 1 more Smart Citation
“…(1), (6), and (9), respectively. The calculated and the experimentally measured cracking angles of the tested specimens are presented in Table 2.…”
Section: Inclination Of Torsional Crackingmentioning
confidence: 98%
“…Recently, the use of continuous spiral reinforcement has been extended in RC elements with rectangular cross-sections. RC subassemblages of external beam-column joints, columns and infilled frames with rectangular members and Rectangular Spiral Reinforcement (RSR) as shear reinforcement have been tested under cyclic loading [5,6]. The experimental results of these tests revealed that the application of RSR in many cases improved the overall seismic performance of the examined specimens in comparison with the conventionally reinforced subassemblages [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…The first application of rectangular spiral reinforcement in RC beams was carried out by in an experimental study in 2005. At present, the studies on effectiveness of rectangular spiral shear reinforcement on RC structures have been accelerated (Karayannis and Sirkelis, 2005a;Tsonos, 2007;Kakaletsis et al, 2011). In 2011, an experiment was conducted by Yang et al (Yang et al, 2011) on shear behaviour of RC T-beams reinforced by spiral-type wire ropes as internal shear reinforcements.…”
mentioning
confidence: 99%
“…Option (a) is relatively cheap and easier to employ, yet several inherent features of the frame configuration result in deviation from the actual response of the base frame of a multi-story structure. The axial compressive forces of the columns, coming from the dead and live loads of the upper stories, can be applied using hydraulic jacks [21,22]. On the other hand, the actual bending moment at the top of the column as well as the beam-column joint rotation of the prototype multi-story structure, cannot be easily reproduced.…”
Section: General Remarks and Limitations Of Experimental Setupmentioning
confidence: 99%
“…According to Prota et al [31], the main features of the aforementioned model are sufficiently efficient at modeling the cyclic curves of smooth steel bars at L/D ratio ranges below 8, which is the case for the experiments investigated herein. Finally, the existence of common-type or spiral shear reinforcement in various specimens was not investigated in detail, since the results of the physical experiments did not reveal significant effect on the obtained response as described by Kakaletsis et al [22].…”
Section: Numerical Simulation Scheme and Sen-sitivity Analysismentioning
confidence: 99%